THE EFFECT OF DIGITAL MARKETING ON PURCHASING DECISIONS FOR MSME PRODUCTS IN THE SOCIETY 5.0 ERA: A STUDY OF SHOPEE USERS IN YOGYAKARTA - Dara Kusumawati; Dixian Bhikuning; Dison Librado (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2025)
The Society 5.0 era is characterized by deep integration of digital technologies into everyday life, creating both opportunities and challenges for Micro, Small, and Medium Enterprises (MSMEs) in marketing their products. In Yogyakarta, many MSMEs utilize Shopee as a major e‑commerce platform to promote and sell their products to a wider market. Digital marketing activities on Shopee such as storefront and content management, product descriptions, platform‑based promotions, and the use of ratings and reviews have become key strategies to influence consumer purchasing decisions. This article conceptually analyzes the effect of Shopee‑based digital marketing on purchasing decisions for MSME products in the Society 5.0 era, focusing on Shopee users in Yogyakarta. Digital marketing is conceptualized through social media and Shopee‑based e‑commerce activities, while purchasing decision is measured through information search, alternative evaluation, purchase decision, and post‑purchase evaluation. The study employs a three‑step literature‑based method: identifying key concepts, reviewing empirical studies from Indonesia and abroad, and synthesizing findings into an integrated explanation. The review shows consistent evidence that digital marketing positively and significantly affects purchasing decisions and SME performance, with trust, perceived risk, and electronic word of mouth acting as important mechanisms. The synthesis suggests that for Shopee users in Yogyakarta, content quality and trust signals are likely more decisive than short‑term price promotions in driving MSME product purchases. This article contributes by offering a platform and location specific framework situated within the Society 5.0 paradigm, enriched with international literature, and by outlining implications, limitations, and directions for future empirical research.​